Special considerations in paediatric burn patients - Sharma Ramesh; Parashar Atul (Indian Journal of Plastic Surgery)
Burn injuries are a major cause of morbidity and mortality in children. In India, the figure constitutes about one-fourth of the total burn accidents. The management of paediatric burns can be a major challenge for the treating unit. One has to keep in mind that "children are not merely small adults"; there are certain features in this age group that warrant special attention. The peculiarities in the physiology of fluid and electrolyte handling, the uniqueness of the energy requirement and the differences in the various body proportions in children dictate that the paediatric burn management should be taken with a different perspective than for adults. This review article would deal with the special situations that need to be addressed while treating this special class of thermal injuries. We must ensure that not only the children survive the initial injury, but also the morbidity and complications are minimized. If special care is taken during the initial management of paediatric burn injuries, these children can be effectively integrated into the society as very useful and productive members.